Discursive Practices and Symbolic Violence Towards the LGBT Community in the University Context - Martínez-Guzmán, Antar; Íñiguez-Rueda, Lupicinio (Paidéia (Ribeirão Preto), 2018)
Symbolic violence against the lesbian, gay, bisexual and transgender (LGBT) community operates in a normalized way and enhances relationships of inequality in diverse social spaces. The objective of this study is to explore forms of symbolic violence against LGBT people committed through the discourse of students and teachers in the context of Mexican universities. A qualitative methodology was adopted involving the use of the discussion group technique. Subsequently, discourse analysis was conducted drawing on psychosocial thinking. The results reveal two discursive strategies that contribute to the reproduction of forms of discrimination and violence against LGBT people: one in the form of carrilla (Mexican slang for making fun), and the other in the form of tropes and rhetorical figures involving the notion of respect. Finally, we highlight the importance of understanding informal and everyday discursive practices to better address this problem in educational institutions.